Internalisasi Nilai-Nilai Aqidah pada Siswa Madrasah Ibtida’iyyah (Studi Multisitus Madrasah Ibtida’iyyah Al-Kautsar dan Madrasah Ibtida’iyyah Ilhamul Qudus Ponorogo) - Rahayu, Afinda; Masduki, Moh.; Abdurrohman, Moh. Asvin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This written research aims to examine the process of internalizing aqidah values ​​in Madrasah Ibtida'iyyah students through a multisite study at Madrasah Ibtida'iyyah Al-Kautsar and Madrasah Ibtida'iyyah Ilhamul Qudus. This research asks three questions, namely: what is the process of internalizing aqidah values ​​in students at Madrasah Ibtida'iyyah Al-Kautsar Ponorogo, what is the process of internalizing aqidah values ​​in students at Madrasah Ibtida'iyyah Ilhamul Qudus Ponorogo, and what are the similarities and differences internalization of aqidah values ​​in students at Madrasah Ibtida'iyyah Al-Kautsar and Madrasah Ibtida'iyyah Ilhamul Qudus Ponorogo. This research is a multisite research study with a descriptive approach, obtaining data through observation, interviews and documentation. The background taken in this research is the problem of students' lack of understanding regarding aqidah values, the influence of technology and modern media which present values ​​that conflict with aqidah and the lack of role of teachers and parents in educating students regarding aqidah values.